Wednesday

April 16, 2014

April 16, 2014

Posted by **stacey graham** on Friday, March 26, 2010 at 9:30am.

- trig -
**LiNnda**, Monday, May 3, 2010 at 10:52amtan^2x(1+cot^x)=1/(1-sin^2x)

tan^2x(1+1/tan^2x)=1/cos^2x

tan^2x+(tan^x/tan^2x)=1/cos^2x

tan^2x+1=1/cos^2x

sin^2x/cos^2x+1=1/cos^2x

(sin^x+cos^2)/cos^2x=1/cos^2x

1/cos^2x=1/cos^2x

**Related Questions**

Math (Trig) - sorry, another I can't figure out Show that (1-cot^2x)/(tan^2x-1)=...

TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...

trig - {tan^2x+cotx divided by tanx-cotx} is equal to {1 divided by sin^2x-cos^...

Math-Trig - 1. Create an algebraic expression for sin(arccosx-arcsin3x) 2. The ...

math - Simplify sin^2x+cos^2x+sec^2x -tan^2x+csc^2x-cot^2x

trig - (1) tan^2x(1+cot^2x)= _____________ (1-sin^2x)

Trig Identities - Proving identities: 1) 1+ 1/tan^2x = 1/sin^2x 2) 2sin^2 x-1 = ...

Trig....... - I need to prove that the following is true. Thanks (2tanx /1-tan^x...

trig - For each expression in column I, choose the expression from column II to ...

Math - What is the first step. Explain please. Which expression is equivalent to...